APPLICATION OF NISBAH FUNCTION IN ELECTRODYNAMICS - Bambang Ruwanto; Maryanto Maryanto (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2002)
Analyzes about characteristics of quotient function Q(x) = (1- x)/(l + x) have been done, where x was scalar variable. The result of the analyzes showed that quotient function had inverse character and it can be developedfor two variables of multiplication or more. Application of quotient function in electrodynamics for calculation of reflection coefficient on reflection wave on boundary plane produces simpleformulation for r TE and r TM. The result is very useful, because mathematics calculation can be done easily.